The Effect of Learning Independence and Learning Motivation on mathematics Learning Outcomes of Grade VIII Studens at MTs Negeri 1 Donggala - Jingga Pramesti; Mustamin Idris; Bakri M Bakri M; Fajriani Fajriani (FKIP - Universitas Riau, 2026)
This study aims to: (1) determine whether learning independence influences the mathematics learning outcomes of grede VIII studens at MTs Negeri 1 Donggala (2) determine whether learning motivation influences the mathematics learning outcomes of grede VIII studens at MTs Negeri 1 Donggala (3) determine whether learning independence influences the mathematics learning outcomes of grede VIII studens at MTs Negeri 1 Donggala. Penelitian ini menggunakan pendekatan kuantitatif dengan jenis penelitian kausal korelasional. Populasi dalam penelitian ini adalah seluruh siswa Kelas VIII MTs Negeri 1 Donggala. The sample comprised 86 students selected through proportional random sampling. Data were collected using a learning-independence questionnaire, a learning-motivation questionnaire, and a mathematics learning-outcomes test. Data were analyzed using multiple linear regression. The results, at a 5% significance level, showed that: (1) learning independence had a significant effect on mathematics learning outcomes, accounting for 35%; (2) learning motivation had a significant effect on mathematics learning outcomes, accounting for 34.6%; and (3) learning independence and learning motivation jointly had a significant effect on mathematics learning outcomes, accounting for 38.4%.